Improving the scientific and methodological support for teaching students the construction sciences based on digital technologies - Soliev Nodirjon Sodirjon ugli (Zien Journals, 2023)
This article deals with the problem of Teaching building sciences in accordance with modern requirements, the creation of methodological support based on modern digital technologies, the advantages of improving the teaching process to the level of digital support are given.
Keywords: Methodological complexes; methodological support; modern technologies